Reducing Tobacco-Related Cancer Incidence and Mortality: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Tobacco use is the leading cause of preventable death in United States, causing more than 440,000 deaths annually and resulting in $193 billion in health-related economic losses each year—$96 billion in direct medical costs and $97 billion in lost productivity. Since the first U.S. Surgeon General's report on smoking in 1964, more than 29 Surgeon General's reports, drawing on data from thousands of studies, have documented the overwhelming and conclusive biologic, epidemiologic, behavioral, and pharmacologic evidence that tobacco use is deadly. This evidence base links tobacco use to the development of multiple types of cancer and other life-threatening conditions, including cardiovascular and respiratory diseases. Smoking accounts for at least 30 percent of all cancer deaths, and 80 percent of lung cancer deaths. Despite the widespread agreement on the dangers of tobacco use and considerable success in reducing tobacco use prevalence from over 40 percent at the time of the 1964 Surgeon General's report to less than 20 percent today, recent progress in reducing tobacco use has slowed. An estimated 18.9 percent of U.S. adults smoke cigarettes, nearly one in four high school seniors smoke, and 13 percent of high school males use smokeless tobacco products. In recognition that progress in combating cancer will not be fully achieved without addressing the tobacco problem, the National Cancer Policy Forum of the Institute of Medicine (IOM) convened a public workshop, Reducing Tobacco-Related Cancer Incidence and Mortality, June 11-12, 2012 in Washington, DC. In opening remarks to the workshop participants, planning committee chair Roy Herbst, professor of medicine and of pharmacology and chief of medical oncology at Yale Cancer Center and Smilow Cancer Hospital, described the goals of the workshop, which were to examine the current obstacles to tobacco control and to discuss potential policy, outreach, and treatment strategies that could overcome these obstacles and reduce tobacco-related cancer incidence and mortality. Experts explored a number of topics, including: the changing demographics of tobacco users and the changing patterns of tobacco product use; the influence of tobacco use on cancer incidence and cancer treatment outcomes; tobacco dependence and cessation programs; federal and state level laws and regulations to curtail tobacco use; tobacco control education, messaging, and advocacy; financial and legal challenges to tobacco control efforts; and research and infrastructure needs to support tobacco control strategies, reduce tobacco related cancer incidence, and improve cancer patient outcomes. Reducing Tobacco-Related Cancer Incidence and Mortality summarizes the workshop.
Keywords: Health and Medicine

Growing Up Tobacco Free: Preventing Nicotine Addiction in Children and Youths - Institute of Medicine (The National Academies Press, 1994)
Tobacco use kills more people than any other addiction and we know that addiction starts in childhood and youth. We all agree that youths should not smoke, but how can this be accomplished? What prevention messages will they find compelling? What effect does tobacco advertising—more than $10 million worth every day—have on youths? Can we responsibly and effectively restrict their access to tobacco products? These questions and more are addressed in Growing Up Tobacco Free, prepared by the Institute of Medicine to help everyone understand the troubling issues surrounding youths and tobacco use. Growing Up Tobacco Free provides a readable explanation of nicotine's effects and the process of addiction, and documents the search for an effective approach to preventing the use of cigarettes, chewing and spitting tobacco, and snuff by children and youths. It covers the results of recent initiatives to limit young people's access to tobacco and discusses approaches to controls or bans on tobacco sales, price sensitivity among adolescents, and arguments for and against taxation as a prevention strategy for tobacco use. The controversial area of tobacco advertising is thoroughly examined. With clear guidelines for public action, everyone can benefit by reading and acting on the messages in this comprehensive and compelling book.
Keywords: Health and Medicine

Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products - Institute of Medicine (The National Academies Press, 2015)
Tobacco use by adolescents and young adults poses serious concerns. Nearly all adults who have ever smoked daily first tried a cigarette before 26 years of age. Current cigarette use among adults is highest among persons aged 21 to 25 years. The parts of the brain most responsible for cognitive and psychosocial maturity continue to develop and change through young adulthood, and adolescent brains are uniquely vulnerable to the effects of nicotine. At the request of the U.S. Food and Drug Administration, Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products considers the likely public health impact of raising the minimum age for purchasing tobacco products. The report reviews the existing literature on tobacco use patterns, developmental biology and psychology, health effects of tobacco use, and the current landscape regarding youth access laws, including minimum age laws and their enforcement. Based on this literature, the report makes conclusions about the likely effect of raising the minimum age to 19, 21, and 25 years on tobacco use initiation. The report also quantifies the accompanying public health outcomes based on findings from two tobacco use simulation models. According to the report, raising the minimum age of legal access to tobacco products, particularly to ages 21 and 25, will lead to substantial reductions in tobacco use, improve the health of Americans across the lifespan, and save lives. Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products will be a valuable reference for federal policy makers and state and local health departments and legislators.
Keywords: Health and Medicine

Environmental Tobacco Smoke: Measuring Exposures and Assessing Health Effects - National Research Council (The National Academies Press, 1986)
This comprehensive book examines the recent research investigating the characteristics and composition of different types of environmental tobacco smoke (ETS) and discusses possible health effects of ETS. The volume presents an overview of methods used to determine exposures to environmental smoke and reviews both chronic and acute health effects. Many recommendations are made for areas of further research, including the differences between smokers and nonsmokers in absorbing, metabolizing, and excreting the components of ETS, and the possible effects of ETS exposure during childhood and fetal life.
Keywords: Health and Medicine; Environment and Environmental Studies

Combating Tobacco Use in Military and Veteran Populations - Institute of Medicine (The National Academies Press, 2009)
The health and economic costs of tobacco use in military and veteran populations are high. In 2007, the Department of Veterans Affairs (VA) and the Department of Defense (DoD) requested that the Institute of Medicine (IOM) make recommendations on how to reduce tobacco initiation and encourage cessation in both military and veteran populations. In its 2009 report, Combating Tobacco in Military and Veteran Populations, the authoring committee concludes that to prevent tobacco initiation and encourage cessation, both DoD and VA should implement comprehensive tobacco-control programs.
Keywords: Health and Medicine

Understanding the U.S. Illicit Tobacco Market: Characteristics, Policy Context, and Lessons from International Experiences - National Research Council (The National Academies Press, 2015)
Tobacco use has declined because of measures such as high taxes on tobacco products and bans on advertising, but worldwide there are still more than one billion people who regularly use tobacco, including many who purchase products illicitly. By contrast to many other commodities, taxes comprise a substantial portion of the retail price of cigarettes in the United States and most other nations. Large tax differentials between jurisdictions increase incentives for participation in existing illicit tobacco markets. In the United States, the illicit tobacco market consists mostly of bootlegging from low-tax states to high-tax states and is less affected by large-scale smuggling or illegal production as in other countries. In the future, nonprice regulation of cigarettes - such as product design, formulation, and packaging - could in principle, contribute to the development of new types of illicit tobacco markets.
Keywords: Behavioral and Social Sciences; Health and Medicine

Taking Action to Reduce Tobacco Use (The National Academies Press, 1998)
Keywords: Health and Medicine

Scientific Standards for Studies on Modified Risk Tobacco Products - Institute of Medicine (The National Academies Press, 2012)
Smoking-related diseases kill more Americans than alcohol, illegal drugs, murder and suicide combined. The passage of the Family Smoking Prevention and Tobacco Control Act of 2009 gave the FDA authority to regulate "modified risk tobacco products" (MRTPs), tobacco products that are either designed or advertised to reduce harm or the risk of tobacco-related disease. MRTPs must submit to the FDA scientific evidence to demonstrate the product has the potential to reduce tobacco related harms as compared to conventional tobacco products. The IOM identifies minimum standards for scientific studies that an applicant would need to complete to obtain an order to market the product from the FDA.
Keywords: Health and Medicine

Dying to Quit: Why We Smoke and How We Stop - Brigham, Janet (The National Academies Press, 1998)
Historians and scientists a few millennia from now are likely to see tobacco as one of the major bafflements of our time, suggests Janet Brigham. Why do we smoke so much, even when we know that tobacco kills more than a million of us a year? Two decades ago, smoking was on the decline in the United States. Now the decline has flattened, and smoking appears to be increasing, most ominously among young people. Cigar smoking is on the rise. Data from a generation of young smokers indicate that many of them want to quit but have no access to effective treatment. Dying to Quit features the real-life smoking day of a young woman who plans to quit—again. Her comments take readers inside her love/hate relationship with tobacco. In everyday language, the book reveals the complex psychological and scientific issues behind the news headlines about tobacco regulations, lawsuits and settlements, and breaking scientific news. What is addiction? Is there such a thing as an addictive personality? What does nicotine do to the body? How does it affect the brain? Why do people stand in subzero temperatures outside office buildings to smoke cigarettes? What is the impact of carefully crafted advertisements and marketing strategies? Why do people who are depressed tend to smoke more? What is the biology behind these common links? These and many fundamental questions are explored drawing on the latest findings from the world's best addictions laboratories. Want to quit? Brigham takes us shopping in the marketplace of gizmos and gadgets designed to help people stop smoking, from wristwatch-like monitors to the lettuce cigarette. She presents the bad news and the not-so-bad news about smoking cessation, including the truth about withdrawal symptoms and weight gain. And she summarizes authoritative findings and recommendations about what actually works in quitting smoking. By training a behavioral scientist—by gift a writing talent—Brigham helps readers understand what people feel when they use tobacco or when they quit. At a time when tobacco smoke has filled nearly every corner of the earth and public confusion grows amid strident claims and counterclaims in the media, Dying to Quit clears the air with dispassion toward facts and compassion toward smokers. This book invites readers on a fascinating journey through the world of tobacco use and points the way toward help for smokers who want to quit. Janet Brigham, Ph.D., is a research psychologist with SRI International in Menlo Park, California, where she studies tobacco use. A former journalist and editor, she has conducted substance use research at the Johns Hopkins University School of Medicine, the National Institute on Drug Abuse, and the University of Pittsburgh
Keywords: Explore Science; Health and Medicine

Assessing the Use of Agent-Based Models for Tobacco Regulation - Institute of Medicine (The National Academies Press, 2015)
Tobacco consumption continues to be the leading cause of preventable disease and death in the United States. The Food and Drug Administration (FDA) regulates the manufacture, distribution, and marketing of tobacco products - specifically cigarettes, cigarette tobacco, roll-your-own tobacco, and smokeless tobacco - to protect public health and reduce tobacco use in the United States. Given the strong social component inherent to tobacco use onset, cessation, and relapse, and given the heterogeneity of those social interactions, agent-based models have the potential to be an essential tool in assessing the effects of policies to control tobacco. Assessing the Use of Agent-Based Models for Tobacco Regulation describes the complex tobacco environment; discusses the usefulness of agent-based models to inform tobacco policy and regulation; presents an evaluation framework for policy-relevant agent-based models; examines the role and type of data needed to develop agent-based models for tobacco regulation; provides an assessment of the agent-based model developed for FDA; and offers strategies for using agent-based models to inform decision making in the future.
Keywords: Health and Medicine